2013
DOI: 10.1084/jem.20130762
|View full text |Cite
|
Sign up to set email alerts
|

Transient regulatory T cell ablation deters oncogene-driven breast cancer and enhances radiotherapy

Abstract: Transient ablation of regulatory T cells in a murine model of breast carcinogenesis inhibits primary tumor and lung metastatic growth and enhances the therapeutic effect of radiotherapy, but not immune checkpoint blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
193
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(207 citation statements)
references
References 48 publications
(56 reference statements)
11
193
2
1
Order By: Relevance
“…Two other studies showed no effects of aPD-1 therapy on PyMT tumor growth. 20,21 However, in these reports, aCTLA-4 single agent treatment was also shown to be ineffective in controlling tumor growth, unlike our results, which showed 50% clinical benefit. This difference may be due to variations in the treatment regimens and/or the utilization of models of different genetic backgrounds (C57BL/6 mice as opposed to FVB mice used in this study).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Two other studies showed no effects of aPD-1 therapy on PyMT tumor growth. 20,21 However, in these reports, aCTLA-4 single agent treatment was also shown to be ineffective in controlling tumor growth, unlike our results, which showed 50% clinical benefit. This difference may be due to variations in the treatment regimens and/or the utilization of models of different genetic backgrounds (C57BL/6 mice as opposed to FVB mice used in this study).…”
Section: Discussioncontrasting
confidence: 80%
“…1518 The MMTV-PyMT model has been used to test CTLA-4 or PD-1 checkpoint inhibition in combination with other therapeutic approaches such as irradiation or inhibition of the tyrosine kinase Axl. 1921 In these studies, combination approaches provided clinical benefit, whereas single-treatment with checkpoint inhibitors was not efficacious. These data suggest the utility of the PyMT model in discovering synergistic immunotherapeutic drug combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Our observation that Treg depletion deterred tumor growth resembles those of others. 40,41 Yet, in these studies the efficacy of Treg ablation monotherapy was higher than in ours. This might be related to different mouse models used, which showed a more complete deletion of FoxP3 C Tregs.…”
Section: Discussioncontrasting
confidence: 62%
“…+ Tregs play a pivotal role in maintenance of immunological tolerance (117) and also produce cytokines, such as RANKL, that promote breast cancer progression and metastasis (118). Th17 cells produce IL-17A and IL-17F, which accelerate CRC progression (discussed above, ref.…”
Section: Foxp3mentioning
confidence: 99%